Towards a Polarised Electorate? : How Polarisation Affects Turnout Decisions in the Belgian Context of Compulsory Voting - Eck, Bjarn; Michel, Elie (Politics of the Low Countries, 2025)
Both ideological polarisation and affective polarisation tend to increase turnout, but we know little about whether these mobilising effects also hold among an electorate characterised by a history of compulsory voting. In fact, theory suggests that the effects of polarisation might be suppressed in this context, for example, because compulsory voting stimulates a civic duty to vote among the electorate. To address this question, the authors focus on turnout decisions in the context of compulsory voting in Belgium, exploiting a question about hypothetical willingness to vote in future voluntary elections. The authors find that affective polarisation increases the likelihood to mobilise voters in the case where compulsory voting is replaced by voluntary voting. The effect of ideological polarisation on such decision is more contrasted. The authors discuss the implications of these findings, which are increasingly relevant considering the recent decision of the Flemish government to abolish compulsory voting at the local level.